Trials: of Antigone and Jesus - Robert, William (Perspectives in continental philosophy, 2010)
Impossible love -- Between nature and culture -- Surviving, forever foreign -- Cryptic crossing -- Touching transcendence, in the flesh -- The tragedy of Christianity